Manajemen Risiko Pada Proyek Pembangunan Jaringan Pipa Air Limbah Komunal - Pratama, Enif Asfarianto; Muhaemin, Aris (Journal of Industrial and Engineering System, 2022)
The sub-zone 5 communal sewerage pipeline construction project has been carried out and has onlybeen realized 41% with physical development of 35% in the 2016 Regional Capital Investment FiscalYear. This project is a project implemented to improve domestic wastewater services from tourismfacilities, hotels, and other public facilities. The treatment system used is a centralized or communalpiping system as well as expanding the wastewater pipe network system in tourist areas. Based on this,a research is needed on the risks that occur during project development. The research was carried outthrough interviews with experienced and skilled personnel, making and distributing questionnaires,testing the results of questionnaire data by testing the validity and reliability of the risks that occurredin the implementation of this project development. The risk obtained in this study is 71. specifications andaddendum provided by the owner), including unacceptable, 50 (70.42%) risk ( quality concrete Pile Anchorge thatdoes not comply with the specifications approved) including undesirable, 9 (12.68%) risk (operational andoverhead costs are high) including acceptable, 4 (5.63%) risk (the use of the funds out of contract) includingnegligible. Risk mitigation is only given to major risk include risk unacceptable and undesirable risk. Based onthe results of the risk management, implemented regulations on ownership of risk (risk ownership) againstperpetrators (project owners, consultants, planners, consultants and contractor supervision) involved in theimplementation